Relationships among blending conditions, size of dispersed phase, and oil resistance in natural rubber and nitrile rubber blends - Chakrit Sirisinha (2018)
The rheological properties, morphology, and oil resistance in natural rubber and nitrile-butadiene rubber (NR/NBR) blends are investigated as functions of the blending conditions. It is found that the Mooney viscosity of the blends depends more strongly on the blending time than the rotor speed. The size of the NR dispersed phase is approximately independent of the rotor speed, but it decreases with increasing blending time up to 25 min. With a further increase in the blending time the NR dispersed phase size decreases. The results for the relative tensile strength, which is an indicator of oil resistance, are in agreement with those of the blend morphology, indicating that the oil resistance in a 20/80 NR/NBR blend strongly depends on the phase morphology of the blend. The smaller the size of NR dispersed phase, the higher the blend resistance to oil.